2002
DOI: 10.1055/s-2002-19889
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use of Nerve Conduits in Peripheral-Nerve Repair: Review of the Literature

Abstract: The use of nerve conduits has evolved from a previous experimental idea to a clinical reality over the last ten years. An overview of the literature on the clinical use of nerve conduits in peripheral-nerve repair is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
176
0
12

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(188 citation statements)
references
References 48 publications
(63 reference statements)
0
176
0
12
Order By: Relevance
“…The majority of these devices have been variations of hollow conduits, designed to guide regenerating axons toward the distal nerve stump [2,17,30]. Most clinical studies have examined the use of these nerve conduits for sensory nerve gaps of 20 mm or less [9,22]. Weber et al have reported their results after using a polyglycolic acid nerve conduits for the treatment of nerve injuries distal to the wrist crease.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these devices have been variations of hollow conduits, designed to guide regenerating axons toward the distal nerve stump [2,17,30]. Most clinical studies have examined the use of these nerve conduits for sensory nerve gaps of 20 mm or less [9,22]. Weber et al have reported their results after using a polyglycolic acid nerve conduits for the treatment of nerve injuries distal to the wrist crease.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have documented the effectiveness of nerve conduits for short gaps (9); however, the clinical value of nerve conduits to bridge larger gaps remains unclear. (3,9) Recent advances in allograft tissue processing have eliminated the need for immunosuppression, and allografts are becoming an attractive alternative to autografts and conduits. (10,11,12) Several authors have reported success with processed nerve allografts.…”
Section: Introductionmentioning
confidence: 99%
“…Substantially larger segmental defects could be reconstructed, and the morbidity of harvesting would be eliminated. Several types of materials have been proposed as peripheral nerve substitutes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], including autologous materials such as vein and muscle strips, synthetic materials such as polylactic acid and polyglycolic acid, non-autologous biological materials such as acellular peripheral nerve allograft, and conduits made of collagen, laminin, fibronectin, and alginate.…”
Section: Introductionmentioning
confidence: 99%